No difference in clinical outcome and survivorship after total knee arthroplasty with patellar resurfacing and nonresurfacing after minimum 10-year follow-up. Issue 11 (March 2020) - Feng, Bin; Ren, Yi; Lin, Jin; Jin, Jin; Qian, Wenwei; Weng, Xisheng
Abstract : Abstract: The study aims to evaluate the clinical outcomes and surgery survivorship for over 10 years following patellar resurfacing or nonresurfacing in total knee arthroplasty (TKA) in a cohort of Chinese patients. From 1998 to 2003, 355 patients underwent primary TKA in our institute. The survivorship of TKA between the patellar resurfacing and nonresurfacing groups and the clinical outcome of Hospital for Special Surgery knee score, Western Ontario and McMaster Universities index score, patellar score, patellar related complications, and radiological results were studied at latest follow-up. There was no statistically significant difference for the Hospital for Special Surgery score, Western Ontario and McMaster Universities score, and the patellar score between the 2 groups after an average 12.4-year follow-up. Nonresurfacing group had higher anterior knee pain than the resurfacing group (13.2% vs 5.6%). The patients with rheumatoid arthritis had a 2.9-fold higher rate of patellar-related complications than did the patients with osteoarthritis. The 10-year survival rate was not significantly different between the 2 groups both for revision surgery ( P  = .505) and for patellar-related complication ( P  = .194). There was no significant difference in the long-term clinical outcome and survivorship between patellar resurfacing and nonresurfacing. Patellar nonresurfacing could be advisable during primary TKA for osteoarthritis patients. Selective patellar resurfacing for RA patients could achieve lower patellar-related complications.